ENSURING PSYCHOLOGICAL SAFETY IN INCLUSIVE EDUCATION AND ITS SOCIO-PEDAGOGICAL ASPECTS - Umarova Mehrinisa Sherali qizi (Bright Mind Publishing, 2025)
This article highlights the theoretical and practical aspects of ensuring psychological safety in an inclusive education system, analyzes the socio-pedagogical foundations of creating a safe, humane educational environment for children with disabilities, shows the role of teacher, parent, and community cooperation in ensuring psychological safety, and substantiates ways to prevent violence in the educational environment, form supportive relationships, and develop social integration.
Keywords: Inclusive education, psychological safety, socio-pedagogical approach, integration, supportive environment.